THE INFLUENCE OF EDUCATIONAL SERVICE QUALITY AND SCHOOL IMAGE ON STUDENT SATISFACTION IN PRIVATE HIGH SCHOOL "X" BANDUNG CITY - Cecilia, Stephanie; Saputra, Bobby Wiryawan (International Journal of Social Service and Research, 2024)
This study aims to determine the influence of the quality of educational services, student satisfaction, and school image on student satisfaction at Private High School (SMA) "X" Bandung City, West Java. The population in this study is all students in grades X, XI, and XXII totaling 99 students, and 2023 alumni totaling 28 people (a total of 127 respondents). The results of the analysis and discussion were as follows: (1) The quality of education services has a positive and significant influence on the satisfaction of students at private high school with a total influence of 32.0%. (2) In addition, school image also has an important influence on students' satisfaction, which is 36.5%. (3) The school's image has also a significant positive influence on satisfaction with an overall influence of 68.5%, and it is recommended that schools provide continuous professional training and development for teachers to improve knowledge, skills, pedagogy.